759 Platypnoea orthodeoxia syndrome following middle-lower bilobectomy: a case report. (8th December 2021) - Spontoni, Paolo; Stazzoni, Laura; Giannini, Cristina; Costa, Giulia; Angelillis, Marco; Giannini, Danilo; De Carlo, Marco; Pieroni, Andrea; Petronio, Anna Sonia
Abstract: Aims: PlatypneaOrthodeoxiasyndrome (POS) is a rare clinical condition characterized by dyspnoea and arterial desaturation, typically occurring in orthostatism and vanishing in a supine position. The real pathophysiologic triggers are still not completely understood. Methods and results: In January 2021, a 76-year-old female patient was admitted to our department for the management of a large mass in the right lung (69 × 54 × 76 cm). Pre-operative Computed Tomography (CT)-scan showed a lesion of the right lower lobe, with suspected infiltration of posterior costal pleura and bronchoscopy revealed distal occlusion of intermedious bronchus. Surgical treatment was planned: extrapleural lower bilobectomy with the removal of the VI rib to reduce intracavity space was performed, using postero-lateral thoracotomy approach. On the third post-operative day, an acute neurologic deficit with left-sided paralysis, associated with desaturation and hypotension, occurred during a new attempt to mobilize the patient. Nonetheless the patient showed complete resolution of symptoms in supine position. A new similar episode of severe desaturation (SO2 80%) was observed in the 7th post-operative day. Arterial blood gas test showed PO2 37 mmHg; PCO2 27 mmHg; SO2 80.3%, pH 7.61, tHb 12.4 g/dl; O2 Hb 78.4%. CT pulmonary angiography excluded a suspicious of pulmonary embolism. A right to left atrial shunt was suspected. Contrast-enhanced transcranial Doppler ultrasound showed microembolic signals in the basal cerebral arteries. Transoesophageal echocardiography was performed, confirming an interatrial septum with an exuberant hyperdynamic movement and showing an abundant passage of contrast from the right atrium to the left, even without the Valsalva manoeuvre, compatible with an important patent foramen ovale (PFO). Patient was referred to the cardiac Catheterization Laboratory for percutaneous closure of PFO. The device was successfully placed via right femoral venous catheter access and on transesophageal echocardiogram guidance. The procedure was performed without any complications. The implanted device was noted to be in a stable position with trivial residual inter-atrial shunting immediately after the procedure. The day after implantation, positional discomfort improved remarkably and the patient was able to stand-up with no symptoms, maintaining normal saturation (SaO2 100%). The patient was discharged and sent home on the third post-implantation day. The 4 month follow-up examination showed a good andstable condition. Conclusions: Platypnoea Orthodeoxia Syndrome after lobectomy is a rare cause of postoperative dyspnoea/hypoxia.It is the result of right-to-left shunt via interatrial communication. Mediastinal relocation, stretching of the atrial septum are among the functional elements necessary for the clinical manifestations. It is essential to have a high index of suspicion to detect POS in patient with dyspnoea given the subtle and positional nature of the symptoms. Physicians should always consider POS in patients with unexplained dyspnoea; hence the treatment modalities could alleviate symptoms and be potentially curative.